1995
DOI: 10.1007/bf01875051
|View full text |Cite
|
Sign up to set email alerts
|

Concise overview of the clinical pharmacokinetics of dideoxynucleoside antiretroviral agents

Abstract: In this paper aspects of the clinical pharmacokinetics of the antiretroviral agents zidovudine, didanosine and zalcitabine are reviewed. Special attention is paid to possibly altered pharmacokinetics in special circumstances, such as hepatic and renal dysfunction, pregnancy, stage of disease, etc, The dideoxynucleoside antiretroviral agents have some clinical pharmacokinetic properties in common (rapid absorption and elimination), but substantial differences exist in their degree of absorption, metabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…d4T, ddC, ZDV and ddI were provided by Sigma (Taufkirchen, Germany). The drugs were used at concentrations close to their C max values: ZDV 1 µM [23], d4T 10 µM [24], ddI 10 µM [25] and ddC 0.2 µM [26].…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…d4T, ddC, ZDV and ddI were provided by Sigma (Taufkirchen, Germany). The drugs were used at concentrations close to their C max values: ZDV 1 µM [23], d4T 10 µM [24], ddI 10 µM [25] and ddC 0.2 µM [26].…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Correlation exists between the onset of constitutional symptoms of AIDS and the level of CD 4 + T cells in HIV patients (Fauci et al 1985, Bacchetti andMoss 1989). Many studies have also demonstrated that this destruction of CD 4 + T cells population results in a critical immune deficiency that allows for the development of a wide range of opportunistic infections and tumors Fauci 1987, Mc Dougal andMoss 1985) Azidothymidine (AZT) is an antiretroviral drugs which inhibits HIV DNA replication in the CD 4 + T cells and thus has been used in the prophylactic treatment of AIDS symptoms (Sattentau, Claphan, & Weisis, 1988, Englund and Baker, 1997, Burger and Meenhorst, 1995andHammer, 1997. The therapeutic effectiveness of AZT was demonstrated in Caucasians whose AIDS disease is associated with HIV -1 (Yoffe and Fauci, 1987).…”
mentioning
confidence: 99%
“…The use of phenotypic assays to determinate drug susceptibilities of the patient's viral isolates in vitro, where available, limits the need to understand the relationships between viral genotypes and phenotypes, but may be misleading because the samples are not completely representative of the patient's entire viral population [11,12]. Furthermore, the concentrations of antiretroviral drugs used in vitro may not correlate with the concentrations of free and active drug in the body [13][14][15].…”
mentioning
confidence: 99%